2002
DOI: 10.1007/s005200100277
|View full text |Cite
|
Sign up to set email alerts
|

Fever and neutropenia in children with solid tumors is similar in severity and outcome to that in children with leukemia

Abstract: There is growing interest in developing criteria that will allow efficient prospective discrimination between cancer patients at high and at low risk for complex fever and neutropenia. The objective of this study was to determine whether there were differences in patterns of documented infections and outcome of episodes of fever and neutropenia in pediatric patients with leukemia and those with solid tumors, a potential risk factor. A total of 283 febrile neutropenia episodes in pediatric cancer patients at a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 27 publications
3
20
0
1
Order By: Relevance
“…Overall, nine patients (26%) were hospitalized for management of fever and neutropenia within the study period. This rate is comparable to the reported rate in the literature with respect to aggressive ALL and solid tumor protocols 13–16, suggesting that there is no increased risk to patients in this setting. Only one patient (3%) had definitive evidence of microbial infection.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, nine patients (26%) were hospitalized for management of fever and neutropenia within the study period. This rate is comparable to the reported rate in the literature with respect to aggressive ALL and solid tumor protocols 13–16, suggesting that there is no increased risk to patients in this setting. Only one patient (3%) had definitive evidence of microbial infection.…”
Section: Discussionsupporting
confidence: 82%
“…Leukemia is not generally included in low‐risk groups because bone marrow suppression is more severe and of longer duration 28–31 . However, some studies have reported that the course of febrile neutropenia did not differ in leukemia and solid tumors 32 . Fanci et al.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31] However, some studies have reported that the course of febrile neutropenia did not differ in leukemia and solid tumors. 32 Fanci et al suggested that piperacillin-tazobactam might be a reasonable option in patients with acute leukemia. 33 Recently, satisfying results with monotherapy in high-risk groups were also informed.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Children with hematologic malignancies have been considered at increased risk of FN, although other studies show that solid tumors have the same pattern of FN severity and outcomes. 11 Moreover, it has also been reported that malnutrition, number of previous chemotherapy regimens of >3, and combination chemotherapy with >3 drugs were associated with FN onset in children and adults with bone and soft-tissue sarcoma. 12 In our clinical setting, a large number of pediatric patients receiving CDDPBC develop FN and creates a health problem.…”
mentioning
confidence: 99%